Hirschsprung Disease: Critical Evaluation of the Global Research Architecture Employing Scientometrics and Density-Equalizing Mapping - Schöffel, Norman; Gfroerer, Stefan; Rolle, Udo; Bendels, Michael H. K.; Klingelhöfer, Doris; Groneberg-Kloft, Beatrix (European Journal of Pediatric Surgery, 2017)
Introduction Hirschsprung disease (HD) is a congenital bowel innervation disorder that involves several clinical specialties. There is an increasing interest on the topic reflected by the number of annually published items. It is therefore difficult for a single scientist to survey all published items and to gauge their scientific importance or value. Thus, tremendous efforts were made to establish sustainable parameters to evaluate scientific work within the past decades. It was the birth of scientometrics.Materials and Methods To quantify the global research activity in this field, a scientometric analysis was conducted. We analyzed the research output of countries, individual institutions, authors, and their collaborative networks by using the Web of Science database. Density-equalizing maps and network diagrams were employed as state of the art visualization techniques.Results The United States is the leading country in terms of published items (n = 685), institutions (n = 347), and cooperation (n = 112). However, although there is dominance in quantity, the most intensive international networks between authors and institutions are not linked to the United States. By contrast, most of the European countries combine the highest impact of publications. Further analysis reveal the influence of international cooperation and associated phenomena on the research field HD.Conclusion We conclude that the field of HD is constantly progressing. The importance of international cooperation in the scientific community is continuously growing.
Keywords: congenital megacolon; scientometrics; Hirschsprung disease; density-equalizing mapping; self-citation